2012
DOI: 10.1590/s1516-05722012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Concentrações de BAP sobre a proliferação in vitro de brotos de Lippia alba [(Mill.)N.E.Brown]

Abstract: Lippia alba é uma planta de origem brasileira, pertencente à família Verbenaceae. É conhecida por combater a insônia e a asma, além de possuir ação anticonvulsivante e antifúngica. A micropropagação tem sido utilizada para multiplicação de várias espécies com propriedades medicinais, e o BAP é a citocinina sintética mais utilizada para a multiplicação in vitro. O objetivo deste trabalho foi estabelecer a concentração adequada de BAP na multiplicação in vitro de L. alba. Explantes constituídos de segmentos noda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Similar results were observed in blackberry plants, with maximum leaf development (7.89) in the presence of 1.0 mg L -1 BAP (Villa et al, 2005), and in Dendrobium nobile seedlings, with the greatest number of leaves (5.47) in the presence of 2.7 mg L -1 BAP (Soares et al, 2011). These results disagree with those recorded in nodal segments of Lipia alba, where the greatest number of leaves was observed in the absence of BAP (Asmar et al, 2012). According to the authors, this cytokinin promotes a greater number of small-sized buds, showing a smaller number of nodal segments and leaves, an effect that was not observed in this study.…”
Section: Resultsmentioning
confidence: 85%
“…Similar results were observed in blackberry plants, with maximum leaf development (7.89) in the presence of 1.0 mg L -1 BAP (Villa et al, 2005), and in Dendrobium nobile seedlings, with the greatest number of leaves (5.47) in the presence of 2.7 mg L -1 BAP (Soares et al, 2011). These results disagree with those recorded in nodal segments of Lipia alba, where the greatest number of leaves was observed in the absence of BAP (Asmar et al, 2012). According to the authors, this cytokinin promotes a greater number of small-sized buds, showing a smaller number of nodal segments and leaves, an effect that was not observed in this study.…”
Section: Resultsmentioning
confidence: 85%
“…In general, the in vitro plant regeneration procedure involved the use of growth regulators even when axillary buds were used as explants [19,20,48,49,50]. In L. alba, for example, the cytokinin BAP has been used in the cultivation of nodal segments with the purpose of rapid multiplication [39,40,41]. We demonstrated that L. alba does not require supplemental growth regulators for in vitro maintenance as was reported for other species such as plant regeneration procedure involved the use of growth regulators even when axillary buds were used as explants , for example, the cytokinin BAP has been used in the cultivation of nodal segments with the purpose of rapid iplication [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In L. alba, for example, the cytokinin BAP has been used in the cultivation of nodal segments with the purpose of rapid multiplication [39,40,41]. We demonstrated that L. alba does not require supplemental growth regulators for in vitro maintenance as was reported for other species such as plant regeneration procedure involved the use of growth regulators even when axillary buds were used as explants , for example, the cytokinin BAP has been used in the cultivation of nodal segments with the purpose of rapid iplication [39,40,41]. We demonstrated that does not require supplemental growth maintenance as was reported for other species such as Bacopa monnieri [14] and Scutellaria baicalensis The authors demonstrated the propagation of axillary buds on hormone-free MS medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation